Users Also Read

MCQ's Search Engine

Electrical Engineering

Mechanical Engineering

Civil Engineering

Automobile Engineering

Chemical Engineering

Computer Engineering

Electronics Engineering

Medical Science Engg

Q1. | If '-' stands for 'division', '+' for 'multiplication', '÷' for 'subtraction' and 'x' for 'addition', which one of the following equations is contct ? |

A. | 6 + 20 - 12 ÷ 7 1 = 38 [Wrong Answer] |

B. | 6 - 20 ÷ 12 x 7 + 1 = 57 [Wrong Answer] |

C. | 6 + 20 - 12 ÷ 7 x 1 = 62 [Wrong Answer] |

D. | 6 ÷ 20 x 12 + 7 - 1 = 70 [Correct Answer] |

View Answer
Explanation:-
Answer : DDiscuss it below :!! OOPS Login [Click here] is required to post your answer/resultHelp other students, write article, leave your comments |

**Also Read Similar Questions Below :**

⇒ If x means ÷, - means x, ÷ means + and + means -, then (3 - 15 ÷ 19) x 8 + 6 = ?

-1

2

4

8

⇒ If A + B = 2C and C + D = 2A, then

A + C=B+D

A + C = 2D

A + D=B+C

A + C = 2B

⇒ If Q means 'add to', J means 'multiply by', T means 'subtract from' and K means 'divide by', then 30 K2Q3J6T5=?

18

28

31

103

⇒ If '-' stands for 'division', '+' for 'multiplication', '÷' for 'subtraction' and 'x' for 'addition', which one of the following equations is contct ?

6 + 20 - 12 ÷ 7 1 = 38

6 - 20 ÷ 12 x 7 + 1 = 57

6 + 20 - 12 ÷ 7 x 1 = 62

6 ÷ 20 x 12 + 7 - 1 = 70

⇒ If + means -, - means x, ÷ means + and x means ÷, then 15 - 3 + 10 x 5 ÷ 5 =?

5

22

48

52

⇒ If A + B> C + D, B + E = 2C and C + D > B + E, it necessarily follows that

A + B > 2E

A + B > 2C

A > C

A + B > 2D

⇒ If P means 'division', T means 'addition', M means 'subtraction' and D means 'multiplication': then what will be the value of the expression 12 M 12 D 28 P 7 T 15?

-30

-15

15

45

⇒ If A > B, B> C and C > D, then which of the following conclusions is definitely wrong ?

A > D

A > C

D > A

B > D

⇒ If A+B=C+D and A + D > B + C, then which one of the following is definitely wrong ?

A > B

A > C

C > D

B > D

⇒ If + means ÷, ÷ means -, - means x, x mearts +, then 12 + 6 ÷ 3 - 2 x 8 = ?

-2

2

4

8